Effect of planting date on the incidence of eggplant aphid, Aphis gossypii Glover and yield of eggplant (Bangladesh Journal of Zoology, 2012)
Impact of planting dates on Aphis gossypii Glover infestation and yields of eggplants was studied in the field. The aphid population was very low (4.75-31.05 aphids/plant) on the first planted crops. Yield of first planting dates were higher (1.56-3.58 kg/plant), however; aphid population on the successive late planting crops gradually increased and reached to peaks at third planting dates (15.51- 96.46 aphids/plant). Yield of eggplant gradually decreased on successive late planting crops and lowest yield recorded for third planting crops (1.06-1.88 kg/plant).DOI: http://dx.doi.org/10.3329/bjz.v39i2.10585 Bangladesh J. Zool. 39(2): 187-194, 2011